Fluffy honeycomb-like activated carbon from popcorn with high surface area and well-developed porosity for ultra-high efficiency adsorption of organic dyes. (August 2019) - Yu, Yun; Qiao, Ning; Wang, Danjun; Zhu, Qizhen; Fu, Feng; Cao, Ruiqi; Wang, Ran; Liu, Wei; Xu, Bin
Graphical abstract: Fluffy honeycomb-like activated carbon material was successfully prepared from popcorn via a simple NaOH activation process, which exhibited ultra-high specific surface area, well-developed pore structure and excellent adsorption capacity for organic dyes. Highlights: Fluffy honeycomb-like activated carbon is prepared from popcorn by NaOH. It shows ultra-high surface area and developed hierarchical porous structure. The carbon exhibits outstanding adsorption capacity for various organic dyes. The carbon presents very quick dye adsorption capability. Abstract: Fluffy honeycomb-like activated carbon with ultra-high surface area and well-developed hierarchical porous structure is simply prepared from popcorn by NaOH activation as adsorbent for dye removal. The popcorn has an unique fluffy structure, which originates from the corn via a rapid puffing process and is reserved during the following carbonization and NaOH activation. The ultra-high surface area and developed hierarchical porous structure make PDAC-4 show an outstanding adsorption capacity of 7765 mg·g −1 for Rhodamine B (2500 mg·L −1 ), which is several times higher than those of the adsorbents ever reported. Moreover, PDAC-4 also has excellent adsorption performance for other dyes, such as Congo Red, Methylene Blue and Methyl Orange. The superior adsorption performance of PDACs to organic dyes opens its potential application in the purification of dye wastewater.